KENDALA PEMBELAJARAN MATEMATIKA SECARA DARING DAN LURING SAAT PANDEMI COVID-19 TERHADAP SISWA AUTIS - Putra, Eric Dwi; Lutfiyah; Ramadhan, Yustin Shinda Putri (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
This research aims to describe the obstacles to online and offline mathematics learning for autistic students in class VIII SMPLB Bintoro Jember. This research conducted was qualitative research through a descriptive approach. The subjects were the class teacher. The collection of data using interviews and documentation studies. Data analysis with data reduction stages and then data presentation after that drawing conclusions. The validity of the data using triangulation techniques. The research obtained the following results: (1) Implementation of online and offline mathematics learning for autistic students in class VIII SMPLB Bintoro Jember which was carried out by class teachers assisted by smartphones with the WhatsApp application. (2) The difficulties experienced by teachers in implementing online mathematics learning for autistic students in class VIII, which consist of student factors themselves, student focus and an environment that is different from school. (3) The factors that cause a decrease in learning outcomes in autistic students, which consist of limited time, cellphone and signal constraints and parents who cannot accompany autistic students in learning because they are busy. The conclusion obtained was that there was a decrease in the mathematics learning outcomes of class VIII autistic students before the pandemic with an average of 74.75, while during the pandemic it was an average of 70.75. Even though there are several obstacles in learning that cause a decrease in the value obtained by autistic students in learning during a pandemic as much as 4%, the implementation of online learning can be stated as good and smooth with the help of a smartphone using the WhatsApp application.